Potential of a Biofertilizer to Control Peregrinus maidis (Hemiptera: Delphacidae), an Insect Vector of Maize Mosaic Alphanucleorhabdovirus - Alviar, Karen B.; Zarate, Jocelyn T.; Yap, Sheryl A.; Albez, Rickson C.; Barbin, Arabelle Izza (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The use of biofertilizers in combination with synthetic fertilizer has been effective in managing the population of Peregrinus maidis. The impact of a biofertilizer was assessed through the response of P. maidis. Corn plants were planted in potted soil with four different treatments. Plant defensin expression was determined using semi-quantitative PCR analysis, while lugensin expression in insects was analyzed using two-step semi-quantitative RT-PCR. Defensin is shown to be expressed in corn upon insect infestation on both biofertilizer Mykoplus and a combination of urea and complete fertilizers. The plants treated with the combination of urea and complete fertilizer had similar numbers of insects (25%) to plants treated with biofertilizer alone. It was worth noting that although female macropters preferred biofertilizer-treated plants for oviposition, their preference in plants treated with urea and complete biofertilizer is not significantly different. Interestingly, the corn plants treated with biofertilizer plus urea had a similar number of oviposited eggs among the treatments (P=0.8166). This research presents novel results as it explores the potential benefits of using biofertilizers as a biocontrol method to manage the population of insect vectors that transmit a viral phytopathogen affecting corn.